2010
DOI: 10.1158/0008-5472.can-10-1439
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Expression of Hypoxia-Inducible Factor-1α Suppresses T-Cell Function and Promotes Tumor Progression

Abstract: T cells can inhibit tumor growth, but their function in the tumor microenvironment is often suppressed. Many solid tumors exhibit abundant macrophage infiltration and low oxygen tension, yet how hypoxic conditions may affect innate immune cells and their role in tumor progression is poorly understood. Targeted deletion of the hypoxia-responsive transcription factor hypoxia-inducible factor-1α (HIF-1α) in macrophages in a progressive murine model of breast cancer resulted in reduced tumor growth, although vascu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
480
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 566 publications
(494 citation statements)
references
References 49 publications
10
480
2
2
Order By: Relevance
“…On the same note, Doedens and colleagues reported that macrophage expression of HIF1a suppresses T-cell function and promotes tumor growth (40). On the basis of the results observed in the present study showing the important role of PI3K signaling axis in controlling both HIF1a and HIF2a accumulation in macrophages, we hypothesize that PI3K signaling should promote tumor growth by increasing secretion of proangiogenic factors in TAMs.…”
Section: Pi3kg Signaling In Macrophages Promotes Tumor Growth and Metsupporting
confidence: 84%
“…On the same note, Doedens and colleagues reported that macrophage expression of HIF1a suppresses T-cell function and promotes tumor growth (40). On the basis of the results observed in the present study showing the important role of PI3K signaling axis in controlling both HIF1a and HIF2a accumulation in macrophages, we hypothesize that PI3K signaling should promote tumor growth by increasing secretion of proangiogenic factors in TAMs.…”
Section: Pi3kg Signaling In Macrophages Promotes Tumor Growth and Metsupporting
confidence: 84%
“…HIF-2α was shown to regulate TAM infiltration in murine models of colon and hepatocellular carcinoma [140]. In a model of breast cancer, HIF-1α-deficient TAMs displayed defective capacity to suppress T cell functions [141]. These results endorse the great potential of HIF inhibition in cancer therapy.…”
Section: Molecular Determinants Of Tamcs Functionsmentioning
confidence: 81%
“…As a defining hallmark of the myeloid cell lineage, plasticity allows macrophages to adjust their effector functions to their surrounding environment (49). In response to hypoxic conditions, macrophages modulate their metabolism (50,51), effector functions in inflammatory responses (52), and ability to handle tumor progression or promote T cell stimulation (53). Because PHD3 regulates HIF protein stability (54) and is itself an HIF target gene (25), it can be hypothesized that the differential EGLN3 gene expression in M1(GM-CSF) and M2(M-CSF) macrophages may underlie a distinct response of both macrophage subtypes to hypoxia.…”
Section: Discussionmentioning
confidence: 99%